Exploring the nexus between emotional dissonance, leadership, organizational commitment, job satisfaction and intention to leave among medical professionals in Thailand - JERMSITTIPARSERT, K; URAIRAK, B (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThe main purpose of the current study is to explore the nexus between emotional dissonance, leadership, organizational commitment, job satisfaction and intention to leave. In addition to that, the study has examined the mediating role of job satisfaction in the relationship between leadership and intention to leave and between emotional dissonance and intention to leave.  This study has used the survey-based methodology and the SEM-PLS technique to test the hypothetical relationships. The data was collected from medical professionals in Thailand. The findings of the study provide support to the theoretical foundation and the proposed hypothesis of the current study. RESUMENEl objetivo principal del presente estudio es explorar el nexo entre la disonancia emocional, el liderazgo, el compromiso organizacional, la satisfacción laboral y la intención de renunciar. El estudio también ha examinado el papel mediador de la satisfacción laboral en la relación entre el liderazgo y la intención de renunciar, y entre la disonancia emocional y la intención de renunciar. Este estudio ha utilizado la metodología basada en encuestas y la técnica SEM-PLS para probar las relaciones hipotéticas. Los datos fueron recolectados de profesionales médicos en Tailandia. Los resultados del estudio respaldan los fundamentos teóricos y las hipótesis propuestas para el estudio actual.